Effects of heat treatment on some characteristics of Scots pine (Pinus sylvestris L.) wood - Durmaz, Ekrem; Ucuncu, Tutku; Karamanoglu, Mehmet; Kaymakci, Alperen (BioResources, 2019)
Heat treatment of wood materials is generally performed to improve the physical, mechanical, chemical, surface, thermal, and crystallinity characteristics. In this way, the usage areas of wood material in different purposes can be expanded by means of heat treatment. The goal of this study was to determine the physical, mechanical, chemical, crystallinity, and surface properties of heat-treated Scots pine (Pinus sylvestris L.) wood. The test samples were heat-treated at 120 °C, 150 °C, 180 °C, and 210 °C for 4 and 6 h in a laboratory-scale oven. The shrinking and swelling chracteristics of wood was decreased as a function of heat treatment processes. Bending strength, compression strength, and modulus of elasticity decreased. In addition, lignin ratios and crystallinity index increased as temperature and duration of the treatment were increased. Consequently, heat-treated wood materials can be used in various areas by developing some of their properties.